Drug Therapy for Type 2 Diabetes - Krentz, Andrew; SpringerLink (Online service) (Heidelberg : Springer Healthcare UK : Imprint: Springer Healthcare, 2012)
This Adis Pocket Reference presents an up-to-date, succinct, and practical approach to drug therapy for type 2 diabetes.
Type 2 diabetes: rationale for pharmacological treatment -- Established classes of glucose-lowering drugs -- Recently introduced and emerging classes of glucose-lowering drugs -- The place of newer drugs in treatment algorithms -- Index.
Keywords: Medicine; Toxicology; Diabetes; Medicine & Public Health; Diabetes; Pharmacotherapy; Pharmacology/Toxicology.